2020
DOI: 10.3390/agronomy10101516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Development of Pedotransfer Functions for Predicting Saturated Hydraulic Conductivity for Mexican Soils

Abstract: In the present work, we evaluate the prediction capability of six pedotransfer functions (PTFs), reported in the literature, for the saturated hydraulic conductivity estimations (KS). We used a database with 900 measured samples obtained from the Irrigation District 023, in San Juan del Rio, Queretaro, Mexico. Additionally, six new PTFs were constructed for KS from clay percentage, bulk density, and saturation water content data. The results show, for the evaluated models, that one model presents an overestima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This result can be explained by the following reasons. Based on the Principal Component Analysis of [23], we noted that the principal variables contributing the most to the sample were K S , the percentage of clay, θ S , PWP, and FC, which is supported by the importance plots ( Figure 6). Additionally, for the 900 analyzed samples contained in 10 of the 12 existing types of soil (according to the USDA Textural Soil Classification), they showed that the infiltration rate depended directly on the percentage of clay and the ρ a .…”
Section: Annsupporting
confidence: 55%
See 3 more Smart Citations
“…This result can be explained by the following reasons. Based on the Principal Component Analysis of [23], we noted that the principal variables contributing the most to the sample were K S , the percentage of clay, θ S , PWP, and FC, which is supported by the importance plots ( Figure 6). Additionally, for the 900 analyzed samples contained in 10 of the 12 existing types of soil (according to the USDA Textural Soil Classification), they showed that the infiltration rate depended directly on the percentage of clay and the ρ a .…”
Section: Annsupporting
confidence: 55%
“…In this work, we developed five Artificial Neural Networks in order to calculate the saturated hydraulic conductivity based on the sample used by [23]. All networks consist of one input layer, two hidden layers, and one output layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the study of Trejo-Alonso et al [54], eight new PTFs were developed based on the results of a Principal Component Analysis (PCA). This decision was made due to the fact that only the PTF published by Vereecken et al [36] could be tested and the lack of PTFs for θ s in the literature.…”
Section: Development Of the Ptfs And The Annsmentioning
confidence: 99%